Designing A Circular Value Chain Model for Plastic Waste Upcycling: Case Study in TPS 3R Basama - Nurindrasari, Diana; Putra, IndraLukmana; Suryo, Hendi (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: This research aims to design a circular value chain model that enhances the economic and sustainability potential of plastic waste upcycled into handicrafts. Background Problems: Plastic waste remains a critical environmental issue in Indonesia, and community waste management units such as TPS 3R Basama often face challenges in converting collected materials into valuable products. Research Methods: A mixed-method approach integrates field observations, stakeholder interviews (collectors, managers, and processors), cost and feasibility analysis. Circular Economy principles and value chain frameworks guide the workflow mapping, value-added estimation, and assessment of environmental benefits. Finding/Results: The study shows that implementing a circular value chain model at TPS 3R Basama increases the economic value of plastic waste by up to 12 times while reducing potential landfill residues by 720 kg per year. Conclusion: The circular value chain model is financially and environmentally feasible to enhance TPS 3R productivity as a sustainable circular economy unit.